Study of Crystallization Kinetics of (Fe50Ni50)73.5Si13.5B9Nb3Cu1 Ribbons Prepared by Rapid Cooling Technique - Quang Hoa, Nguyen; Thi Kim Anh, Do; Duy Thien, Nguyen; Van Huy, Hoang; Vinh Thang, Tran; Ngoc Dinh, Nguyen; Thi Ngoc Anh, Tran; Thi Minh Thuy, Luong; Van Hiep, Vuong (VNU Journal of Science: Mathematics - Physics; Vol 39 No 2, 2023)
Amorphous alloy ribbons of (Fe 50 Ni 50 ) 73.5 Si 13.5 B 9 Nb 3 Cu 1 were fabricated by rapid cooling technique on single copper wheel. After fabrication, the crystalline structure of the ribbons were examined by X-ray diffraction method. The results show that the samples possess a complete amorphous state. The crystallization process was studied by using a differential thermal analyzer (DSC). The DSC analysis show that there are two exothermic peaks corresponding to two crystalline phases appeared in the alloy ribbons. By changing the heating rate (i.e. 5, 10, 15, 20 and 25 o C/min) and by using the Kissinger method,  The activation energy of crystallization of the crystalline phases determined for one phase was found to be E 1 = 350 kJ/mol and for other one, E 2 = 375 kJ/mol. Based on these results, we have chosen the appropriate annealing mode for the alloy ribbons. After annealing, the alloy ribbons were achieved nanocrystalline states of FeNi and α-Fe nano-particles with the grain size ranging from 5 to 15 nm and the fraction of crystallization between the crystalline and amorphous phases of 46, 67, 85 and 96 % respectively for the annealing regimes at 500 o C for 20, 30, 50 and 60 minutes.